'The cloak of technicolor': intermedial colour in Antônio das Mortes. (11th March 2019) - Solomon, Stefan
Abstract: While shooting O dragão da maldade contra o santo guerreiro / Antônio das Mortes in 1969, Glauber Rocha turned to colour film. Although it was not the first time he had worked with colour, here the director made special use of Eastmancolor technology in bringing to life the world of Deus e o diabo na terra do sol / Black God, White Devil (1964) that had previously appeared only in black-and-white. In his earlier manifesto, 'The Aesthetics of Hunger' (1965), Rocha had suggested that 'the cloak of technicolor' would not conceal Brazil's social problems, but would rather aggravate them; in this context, his use of colour does not appear as a simple capitulation to the allure of foreign productions, but instead as part of an even deeper concern for the plight of his nation. While in part motivated by the potential to depict his country with an even greater degree of accuracy, Rocha also pointed to the similarities between film and painting in making the switch to colour, and professed an interest in the 'visual integration of colour with music and dance'. The intermedial comparison is an intriguing one, especially considering that while filmmakers like Rocha were reaching for a greater sense of realism, visual artists in Brazil like Hélio Oiticica were following a more conceptual trajectory where colour was concerned. In this environment, emergent forms of chromatic stock in Brazilian cinema in the late-1960s captured both the non-representational and realist aspects of colour, its supplementarity and its indexical connections to the world. Following recent work on intermediality and colour by Sarah Street and Joshua Yumibe, this article considers how the use of new colour technology in Glauber Rocha's filmmaking resonated with certain tropicalist notions about the clash of the archaic and the modern in Brazilian cultural and political history.